MOLECULAR EVOLUTION OF VIRULENCE GENES OF SWINE INFLUENZA VIRUS SUBTYPE-A H1N1:AN ANALYSIS OF HOST RADIATION - RAJU PODDAR; BADVE ABHIJIT SADANAND; KRISHNA KANHAIYA (International Journal of Pharma and Bio Sciences, 2011)
In this research work, we studied the phenomenon of host radiation in Influenza virus subtype-A and subspecies H1N1 between different host species by building a codon based model. Host radiation is influenced by the rates of mutations in their virulence genes. We have analyzed molecular evolution of virulence genes HA, NA, NS1, NS1, PB1, PB2 of swine influenza virus H1N1 from different hosts swine, avian and humans so as to include all hosts. We used a site specific comparison of non-synonymous (amino acid altering) and synonymous (silent) nucleotide substitutions for the 6 selected genes Maximum likelihood genealogies were used to build two hypothesis models Null (H0) and Alternate (H1) hypothesis based on discrete gamma distribution rates. For null hypothesis, we assumed that the rate of change of a site vary with varying rate of gamma distribution and for alternative hypothesis H1, the rate varies with the fixed gamma distribution under codeml program of PAML. Likelihood ratio test was conducted between null and alternate hypotheses. It was found that null hypothesis had a higher rate of substitution and was found to be more suitable for four of the six selected genes. The study showed that HA gene to be having fastest rate of evolving followed by NS1, PB2 and NA gene. Codon usage studies of genes showing virulence according to our model, the most important codons responsible for molecular evolution are Asp and Glu for HA, Asp and Cys for NA, Glu and Thr for NS1, Lys and Arg for PB2 gene.